ASSESSING BUSINESS ENGLISH COMMUNICATION SKILLS THROUGH DIGITAL TASKS - Sunoko Setyawan; Rizqi Febrian Pramudita; Vigo Dewangga (IJEE (Indonesian Journal of English Education), 2026)
The increasing demand for workplace English communication has also increased the need for an evaluation method which is reflective of real professional communication. This research explored the use of digital task-based assessment (DTBA) to assess Business English (BE) communication competence in tertiary education. Based on a convergent mixed-method design, the research participants of the study consisted of 72 undergraduate students of a Business English class at an Indonesian university. Participants completed three digitally mediated assessment tasks: online business presentations, business email writing simulations and virtual meeting role-plays. Quantitative data was obtained by analytic performance rubrics, qualitative data from semi-structured interviews with 15 students. The results showed that students were best at performingtask completion (M = 4.21) and message clarity (M = 4.12), and that fluency (M = 3.88) and virtual meeting role-play performance (M = 3.87) were the most challenging aspects of communication. The results offer initial classroom-based indication that digital TBA (DTBA) can be used to evaluate Business English communication via work-related digital tasks. Indeed, students’ overall impressions of the tasks were that they were real, fun and something they would do in professional communication in the future. However, these results should be interpreted with caution, as the study was not designed to determine full assessment validity. Additional research with larger samples, multiple raters and further validation procedures is required to consolidate theevidence base.